Ekstraksi Minyak Gaharu dengan Pelarut Etanol secara Maserasi - Luthfi , Muhammad Zulfikar; Jerry , Jerry (Politeknik ATI Padang, 2021)
Agarwood is one of the forest products that can be utilized and has a high selling value. Agarwood contains essential oils which have many active compounds and contains a specific aromatic resin that is naturally formed as a form of defense against physical damage or microbial infection. Agarwood essential oil with good quality has a high economic value. This study aims to extract agarwood essential oil using ethanol as a solvent. The optimal yield of agarwood essential oil can be obtained by varying the particle size, the ratio of the weight of the agarwood biomass (kg) to the volume of the solvent (L), and the length of maceration (h). The results showed that the particle size of agarwood did notaffect the yield of agarwood essential oil. The results of the comparison of agarwood biomass with the volume of the solvent showed that the ratio of 1:9 (w/v) obtained the highest yield of 4.02% and the longest maceration time with the highest yield of 4.12% for 72 hours. However, 48 hours of maceration had a greater increase in yield compared to 72 hours of maceration. The increase in yield at 48 hours to 72 hours of maceration was only 0.22% when compared to the increase in yield at 24 hours to 48 hours of maceration, which was 0.56%.